Lord of the fruit flies: an interview with Hugo Bellen - Hugo J. Bellen (The Company of Biologists, 2022)
During his remarkable career, Professor Hugo Bellen has innovated Drosophila genetics and forged a community driven toward diagnosis and treatment of rare diseases. He has advanced our understanding of nervous system development and neurodegeneration by exploring mechanisms and genetics through the latticed eyes of the common fruit fly. His lab, along with the labs of Shinya Yamamoto and Michael Wangler at Baylor College of Medicine and the Jan and Dan Duncan Neurological Research Institute of Texas Children's Hospital in Houston, also function as the Drosophila Core of the Model Organisms Screening Center (MOSC) of the Undiagnosed Diseases Network (UDN) and the Center for Precision Medicine Models. In this capacity, they facilitate the diagnosis of (ultra)rare human diseases and contribute to the development of treatments for these patients. Hugo is also the head of the Drosophila Gene Disruption Project supported by the National Institutes of Health (NIH) Office of Research Infrastructure Programs, and his lab channels substantial resources to the development of novel and sophisticated tools and technology that are then shared openly with the community via the Bloomington Drosophila Stock Center and the Drosophila Genomics Resource Center to propel research across the globe. Hugo has received an array of awards for his contributions to science and medicine, and he continues to be one of the most prominent figures in translational model organism research. In this interview, he discusses how his career progressed towards Drosophila genetics and highlights the accomplishments and challenges faced by the model organism community.